MERWINITE-FACIES MAGNESIAN SKARNS IN XENOLITHS FROM DUNITE OF THE DOVYREN LAYERED INTRUSION - Pertsev N.N.; Konnikov E.G.; Nekrasov A.N.; Kislov E.V.; Orsoev D.A. (My University, 2003)
The late Proterozoic Dovyren dunite-troctolite-gabbro layered massif in the northwestern Baikal area has the morphology of a sill and shows evidence of the replacement of a terrigenous-sedimentary rock sequence, including a 140-m carbonate layer. Relics of the latter are discernible throughout the whole massif in the form of numerous skarn and carbonate xenoliths. Xenoliths in the upper portion of the dunite unit include unique apodolomite spinel-periclase-merwinite skarns, apopericlase brucitites with interstitial spinel and forsterite, and spinel olivinite and spinel monticellitite skarns. The chemistry of the skarn minerals is close to the respective theoretical iron-free end members, which enabled us to apply experimental data to determining their genetic parameters. The merwinite skarns were produced at temperatures above 820°C, pCO2higher than 7 bar at 820°C and lower than ∼100 bar at 1000°C, and assumed pH2O of 500 bar (inferred from geologic reconstructions). The two hypotheses proposed to account for the genesis of the periclasite xenoliths are as follows: contact metamorphism of the brucitites and the preferable extraction of Ca (as compared with Mg) from the primary dolomite in mafic-ultramafic magma.
Keywords: Precambrian::Proterozoic; Докембрий::Протерозой